2022
DOI: 10.1097/spv.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Overactive Bladder Patients With and Without Urgency Incontinence: A Spectrum of One Condition or Different Phenotypes?

Abstract: Importance The importance of this study is to explore potential differences in pathophysiologies of OAB-wet and OAB-dry.Objectives The aim of this study was to define fundamental and unique presenting features of patients exhibiting storage lower urinary tract symptoms (LUTS) with urgency incontinence (OAB-wet) and patients without urgency incontinence (OAB-dry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A recent study of the Lower Urinary Tract Dysfunction Research Network (LURN) cohort revealed that OAB-dry individuals exhibit unique patterns of presenting features that differ from classic OAB subjects, including straining with urination, bladder discomfort, and a feeling of incomplete emptying. 12 The severity of symptomatic bother in these OAB-dry subjects was most closely related to the severity of pelvic floor tenderness on exam, implicating a possible myofascial dysfunction in this LUTS subgroup.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A recent study of the Lower Urinary Tract Dysfunction Research Network (LURN) cohort revealed that OAB-dry individuals exhibit unique patterns of presenting features that differ from classic OAB subjects, including straining with urination, bladder discomfort, and a feeling of incomplete emptying. 12 The severity of symptomatic bother in these OAB-dry subjects was most closely related to the severity of pelvic floor tenderness on exam, implicating a possible myofascial dysfunction in this LUTS subgroup.…”
Section: Introductionmentioning
confidence: 79%
“…This analysis describes the features of that group of highly bothered patients who lacked the bladder pain or urgency incontinence characteristic of IC/BPS or OAB, but were symptomatic with urinary frequency, an uncomfortable urge to void without incontinence and bladder pressure, similar to the OAB-dry subset described within the LURN cohort. 12 In further characterizing this inadequately described phenotype of LUTS, we sought to confirm previously suggested associations with pelvic floor myofascial dysfunction, defining a novel subtype of storage LUTS we termed myofascial frequency syndrome (MFS).…”
Section: Introductionmentioning
confidence: 99%
“…While the name suggests a similar spectrum as OAB, the absence of true urinary urgency is inconsistent with a diagnosis of OAB and suggests a different pathophysiology. A recent study of the Lower Urinary Tract Dysfunction Research Network (LURN) cohort revealed that such “OAB-dry” individuals exhibit unique patterns of presenting features that differ from classic OAB subjects, including straining with urination, bladder discomfort, and a feeling of incomplete emptying 15 . The severity of symptomatic bother in these OAB-dry subjects was most closely related to the severity of pelvic floor tenderness on exam, implicating a possible myofascial dysfunction in this LUTS subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…In the application of our previously described, diagnostic nomogram to a real-world population of subjects with storage LUTS, we hypothesized that the nomogram would successfully identify and classifying subjects with OAB and IC/BPS, but also identify patient subgroups outside the classical LUTS diagnostic paradigm. This analysis describes the features of that group of highly bothered patients who lacked the bladder pain or true urgency characteristic of IC/BPS or OAB, but were symptomatic with urinary frequency, an uncomfortable urge to void without incontinence and bladder pressure, similar to the OAB-dry subset described within the LURN cohort 15 . In further characterizing this inadequately described phenotype of LUTS, we sought to confirm previously suggested associations with pelvic floor myofascial dysfunction, defining a novel subtype of storage LUTS we termed myofascial urinary frequency syndrome (MUFS).…”
Section: Introductionmentioning
confidence: 99%